Biomechanical analysis of the phase structure of Pak Salto on uneven bars - Forminte, V. N.; Cosma, L.; Damian, M.; Dobrescu, T.; Potop, V. (Journal of Physical Education and Sport, 2022)
Purpose. The aim of the paper is to highlight the biomechanical characteristics of the phase structure in the transition from the high bar to the low bar with flight phase - Pak Salto. Material. The comparative biomechanical analysis was carried out during two international competitions, in 2017 and 2018. Seven female gymnasts (14-15 years old) on the uneven bars participated in this research. The comparative computerized video analysis of the phase structure of the transition from the high bar (HB) to the low bar (LB) -Pak Salto - was performed by means of Physics ToolKit program. The Kinovea program was also used to measure the segmental angular characteristics in each key position of the phase structure of Pak Salto execution technique. Results. The key components of the phase structure of the execution technique used for the transition from the HB to the LB with Pak Salto were identified by analyzing the segmental angular characteristics. The results of these angular characteristics of the key components revealed the values of the angle between hip-torso and torso-arms. In order to perform the video analysis, the biomechanical parameters were calculated. The results of the angular velocity in the phase of the preparatory movement indicate a decrease of the value before releasing the bar; in the basic movement phase, at the multiplication of the body posture (MP), the general center of mass (COM) shows an increase in the angular velocity at the toes. In the concluding body posture - final position 1 (CP1) - there is a decrease of the angular velocity of the toes and in CP2 - the angular velocity decreases in all segments. The force in the preparatory movement phase has higher values at the toes and COM. There is a decrease in the shoulders in SPh1 and an increase of the toes force value in SPh2-LP; in the phase of basic movement, at MP - an increase is noticed at the pointed toe; in the concluding body posture, at CP1.1 - there is a decrease in toes and arms; in CP1.2 - a decrease in all body segments. Conclusion. The biomechanical video analysis revealed the spatio-temporal characteristics of the COM trajectory, the value of the angular velocity in relation to the COM and the resultant of the force during the execution of the transition from the HB to the LB with Pak Salto flight phase, according to the method of motion postural cues.